Emergency thoracic surgery in elderly patients - Limmer, Stefan (Royal Society of Medicine Press, 2011)
OBJECTIVES: Emergency thoracic surgery in the elderly represents an extreme situation for both the surgeon and patient. The lack of an adequate patient history as well as the inability to optimize any co-morbidities, which are the result of the emergent situation, are the cause of increased morbidity and mortality. We evaluated the outcome and prognostic factors for this selected group of patients. DESIGN: Retrospective chart review. SETTING: Academic tertiary care referral center. PARTICIPANTS: Emergency patients treated at the Department of Thoracic Surgery, University Hospital of Luebeck, Germany. MAIN OUTCOME MEASURES: Co-morbidities, mortality, risk factors and hospital length of stay. RESULTS: A total of 124 thoracic procedures were performed on 114 patients. There were 79 men and 36 women (average age 72.5 ±6.4 years, range 65–94). The overall operative mortality was 25.4%. The most frequent indication was thoracic/mediastinal infection, followed by peri- or postoperative thoracic complications. Risk factors for hospital mortality were a high ASA score, pre-existing diabetes mellitus and renal insufficiency. CONCLUSIONS: Our study documents a perioperative mortality rate of 25% in patients over 65 who required emergency thoracic surgery. The main indication for a surgical intervention was sepsis with a thoracic/mediastinal focus. Co-morbidities and the resulting perioperative complications were found to have a significant effect on both inpatient length of stay and outcome. Long-term systemic co-morbidities such as diabetes mellitus are difficult to equalize with respect to certain organ dysfunctions and significantly increase mortality.